Increased expression of G9A contributes to carcinogenesis and indicates poor prognosis in hepatocellular carcinoma - Qin, Jian (Oncol Lett, 2018)
Euchromatic histone-lysine N-methyltransferase (G9A), the primary histone methyltransferase for histone H3 Lys(9), has been identified to be upregulated in numerous types of cancer. The aim of the present study was to analyze the clinical significance of G9A, and preliminarily explore its function in hepatocellular carcinoma (HCC). An increased expression level of G9A was demonstrated in the HCC samples and also in 5 publically available datasets. By analyzing GSE14520, it was revealed that its expression level was significantly associated with serum α-fetoprotein level of patients with HCC, and may serve as a potential prognostic indicator for patients with multinodular HCC. Bioinformatics tools were utilized to predict the potential function of G9A, and the results indicated that G9A may modulate gene sets involved in RNA processing and DNA replication. G9A inhibition may suppress cell proliferation by arresting cells in G1 phase and increasing the expression level of microtubule-associated protein light chain 3β (MAP1LC3B) in Huh7 and HepG2 cells. In addition, an inverse association between the expression of G9A and LC3B was demonstrated in HCC tumor samples in the publically available GSE14520 dataset, which indicated that G9A may also have the potential to regulate MAP1LC3B expression in HCC tumor tissues. The results of the present study led to hypothesis that the G9A expression level may be of assistance in diagnosing HCC, and be a potential therapeutic target for HCC. The results provided novel evidence for additional understanding of the crucial role of G9A in tumorigenesis.